La precedencia del pensamiento de F. H. Jacobi en la filosofía hegeliana: Una aproximación al método (Revista Eletrônica Estudos Hegelianos, 2022)
Hegel points to the thought of F. H. Jacobi as one of the precedents of his method. This precedence has doctrinal relevance and logical implications. The objective of our article is to analyze the genesis and dialectical conditions of this precedence. First, we reconstruct the connection of the Hegelian philosophy with Jacobi’s thought from a doctrinal point of view, considering its beginning, its evolution and finally its position as a precedent of the method. Secondly, we will consider the resolution of the doctrinal connection of the Hegelian philosophy with Jacobi’s thought from a logical point of view, analyzing its position in the dialectic of the sublation of the method. Finally, we determine the moments that constitute the precedence of Jacobian thought in the development of Hegelian philosophy.